2020
DOI: 10.1080/15592324.2020.1839710
|View full text |Cite
|
Sign up to set email alerts
|

Differentiate responses of tetraploid and hexaploid wheat (Triticum aestivum L.) to moderate and severe drought stress: a cue of wheat domestication

Abstract: Differentiate mechanism of wheat species in response to contrasting drought stress gradients implies a cue of its long-term domestication. In the present study, three water regimes including well-watered control (WW, 80% field water capacity (FC)), moderate drought stress (MS, 50% FC,) and severe drought stress (SS, 30% FC) were designed to reveal different responses of eight wheat species (four tetraploid and four hexaploid) representing different breeding decades and genetic origins to drought stresses. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Drought stress significantly increased the hydrogen peroxide content in Rosmarinus officinalis. The increase in levels of H 2 O 2 content under drought stress has also been reported in previous studies 51,52 . This increase depends on the severity of the drought stress -SM is related to the increase in the activity of some important enzymes of the oxidative defense system, such as catalas (Figure 7D).…”
Section: The Effect Of Drought Stress and Fe 3 O 4 -Sm Application On...supporting
confidence: 86%
“…Drought stress significantly increased the hydrogen peroxide content in Rosmarinus officinalis. The increase in levels of H 2 O 2 content under drought stress has also been reported in previous studies 51,52 . This increase depends on the severity of the drought stress -SM is related to the increase in the activity of some important enzymes of the oxidative defense system, such as catalas (Figure 7D).…”
Section: The Effect Of Drought Stress and Fe 3 O 4 -Sm Application On...supporting
confidence: 86%
“…Traditionally, crop grain yield would be affected by unfavorable abiotic factors including soil drought stress (Bakhshandeh et al, 2019; Figueroa‐Bustos et al, 2019; Jamieson et al, 1995). In recent years, however, more researches have shown that moderate or mild soil drying would not significantly inhibit crop growth to lower grain yield, but benefit for yield improvement (Fang et al, 2017; Gui et al, 2021; Teng et al, 2022). In this study, change in kernel yield of maize exhibited a simple parabolic trend with the opening down as the soil water potential (SWP) decreased or ABA in roots increased (Table 1; Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…These remained seedlings were treated by one of the water treatments before oviposition selection trials and plant volatile collection. We tested three levels of water treatment: (1) well‐watered treatment (700 mL of water every 4 days), achieving 80%–70% water capacity of the field; (2) moderately water‐stressed treatment (450 mL of water every 4 days), keeping 60%–55% water capacity of the field; and (3) severely watered‐stressed treatment (230 mL of water every 4 days), remaining 40%–35% water capacity of the field (Duan et al, 2021; Gui et al, 2021). There were 20 plastic pots per water treatment for a total of 60 pots.…”
Section: Methodsmentioning
confidence: 99%